Belanja Sekarang, Bayar Nanti: Analisis Shopee Paylater Dalam Perspektif Kaidah-Kaidah Khusus Fiqh Muamalah - Ramadani, Melinda; Al-Kalimantani, Nabila Zahra; Mahendra, Yusril Ihza; Lisnawati, Lisnawati (JISH: Jurnal Ilmu Syariah dan Hukum, 2025)
The use of technology has brought significant changes in the world of electronic commerce (E-Commerce), especially in the payment system. One of the dominant innovations today is the PayLater payment method, which allows consumers to purchase goods or services and pay for them at a later date. This research aims to analyze the Shopee PayLater system from the perspective of the special rules of Fiqh Muamalah, in order to understand its compatibility with Islamic economic principles. The analysis of Shopee PayLater involves an in-depth study of the concept and operational mechanism, as well as a comparison with the principles of Fiqh Muamalah. This research is expected to contribute to a better understanding of the implementation of financial technology in the Islamic context, as well as provide guidance for consumers and service providers in carrying out sharia-compliant transactions.